Home Sanitation and Personal Hygiene as Risk Factors for Leprosy Incidents in Guluk-Guluk District, Madura - Nur Laily Rizki Fajariyah; Imam Thohari; Marlik; Irwan Sulistio; Puspa Wardhani (Public Health Research Development, 2024)
Leprosy is still a health problem in the Guluk-Guluk District. Factors that contribute to the increase in leprosy cases are home sanitation and personal hygiene. House sanitation that does not meet the requirements creates a conducive environment for leprosy bacteria, and inadequate personal hygiene increases the risk of leprosy transmission. This research aims to analyze the relationship between home sanitation and personal hygiene and the incidence of leprosy. This research uses a case-control design. The independent variables are home sanitation and personal hygiene, while the dependent variable is the incidence of leprosy. Data collection is done through interviews, observation, and measurement. The samples used were 30 case samples and 30 control samples. The research location is in the Guluk-Guluk Health Center Working Area. The research time is January - June 2024. Sampling used a simple random sampling technique via lottery. Data were analyzed using chi-square and odds ratio tests. The results show a relationship between house sanitation, ceilings, floors, ventilation, personal hygiene, cleanliness of hands and feet, and the incidence of leprosy. There is no relationship between temperature, humidity, and bed cleanliness with the incidence of leprosy.